Safety and Tolerability of Aripiprazole Lauroxil 2-Month Formulation With 1-Day Initiation for Treatment of Schizophrenia in the ALPINE Study. (April 2021) - Bidollari, Ilda; Vasios, Alexa; Claxton, Amy
Abstract: Objective: Evaluate safety and tolerability of an aripiprazole lauroxil (AL) 2-month regimen using 1-day initiation in patients hospitalized for acute exacerbation of schizophrenia and transitioned to outpatient care. Methods: In the 25-week, double-blind ALPINE study, adults hospitalized for an acute exacerbation of schizophrenia were randomized to AL (AL NanoCrystal Dispersion + oral aripiprazole 30 mg day 1; AL 1064 mg day 8 and q8wk) or the active control paliperidone palmitate (PP 234 mg day 1; PP 156 mg day 8 and q4wk), discharged after 2 weeks if clinically stable, and followed through the end of the study. Adverse events, including adverse events of special interest (AESIs; extrapyramidal symptoms [identified by non-mutually exclusive standardized MedDRA queries], sedation, hypotension, injection site reactions [ISRs], suicidal ideation and behavior) were monitored throughout the study. Results: In total, 200 patients were randomized (AL, n=99; PP, n=101); 99 patients (AL, n= 56; PP, n=43) completed the study. Rates of AESIs in AL-treated patients were akathisia, 10%; Parkinson-like events, 2%; dyskinesia, 3%; dystonia, 9%; sedation, 7%; hypotension, 6%; ISRs, 18 % (including placebo); and suicidal ideation and behavior, 2 %. In PP-treated patients, AESI rates were akathisia, 12%; Parkinson-like events, 4%; dyskinesia, 5%; dystonia, 11%; sedation, 7%; hypotension, 4%; ISRs, 27% (including placebo); and suicidal ideation and behavior, 3%. Conclusion(s): No unexpected safety and tolerability findings were identified in patients treated with AL or PP who were hospitalized for acute schizophrenia exacerbation and transitioned to outpatient care in ALPINE. AESI profiles were consistent with each treatment's respective known safety profile. Funding: Alkermes, Inc. Disclosures: All authors are employees of Alkermes, Inc., and may own stock/options in the company.